For $y=f(-x)$, we reflect $y=f(x)$ in the $y$-axis.

# Reflections $y=-f(x)$ and $y=f(-x)$

For $y=-f(x)$, we reflect $y=f(x)$ in the $x$-axis.

For $y=f(-x)$, we reflect $y=f(x)$ in the $y$-axis.

For $y=f(-x)$, we reflect $y=f(x)$ in the $y$-axis.

For $y=-f(x)$, we reflect $y=f(x)$ in the $x$-axis.

For $y=f(-x)$, we reflect $y=f(x)$ in the $y$-axis.

### Example 1

Consider $f(x)=x^3-4x^2+4x$. On the same axes, sketch the graphs of $y=f(x)$ and $y=-f(x)$. ### Example 2

Consider $f(x)=x^3-4x^2+4x$. On the same axes, sketch the graphs of $y=f(x)$ and $y=f(-x)$. ### Example 3

The function $y=f(x)$ is transformed to $g(x)=-f(x)$. Find the point on $g(x)$ corresponding to the point $(3,0)$ on $f(x)$. ### Example 4

The function $y=f(x)$ is transformed to $g(x)=-f(x)$. Find the point on $f(x)$ that has been transformed to the point $(7,-1)$ on $g(x)$.

For $y=f(-x)$, we reflect $y=f(x)$ in the $y$-axis.

$-f(x)$ means that the graph is to reflect $y=f(x)$ in the $x$-axis, which the sign of $y$-value changes.

Thus the $y$-value $0$ was transformed to $0$.

Therefore the point $(3,0)$ was transformed from $(3,0)$.

Thus the $y$-value $0$ was transformed to $0$.

Therefore the point $(3,0)$ was transformed from $(3,0)$.

$-f(x)$ means that the graph is to reflect $y=f(x)$ in the $x$-axis, which the sign of $y$-value changes.

Thus the $y$-value $-1$ was transformed from $1$.

Therefore the point $(7,-1)$ was transformed from $(7,1)$.

Thus the $y$-value $-1$ was transformed from $1$.

Therefore the point $(7,-1)$ was transformed from $(7,1)$.